Audit committee characteristics and its role in monitoring internal audit function - Mohamad Nor, Mohamad Naimi; Ishak, Suhaimi
The importance of internal audit as internal governance mechanism has been emphasized in the Malaysian Code of Corporate Governance (MCCG) where the companies should establish the internal audit function. To ensure the effectiveness of internal control functions, audit committee is entrusted to monitor andscrutinize internal audit activities. There are several audit committee characteristics that can be considered to determine their effectiveness in monitoring internal audit activities. This article highlighted four characteristics of audit committee that might influence their monitoring role, namely audit committee expertise, business, meeting and independence The article is ended with some suggestions for future research to be undertaken in examining the importance of audit committee and internal audit in Malaysia.